MOLECULAR DOCKING AND MM/GBSA BINDING FREE ENERGY EVALUATION OF NAPROXEN-AZETIDINONE HYBRID DERIVATIVES AS POTENTIAL PREFERENTIAL COX-2 INHIBITORS: COMPARATIVE STUDY WITH MELOXICAM, ISORHAMNETIN, AND NAPROXEN FOR OSTEOARTHRITIS - Moch Ghozi Falih Ar Rammi; Niqia Romah; Imam Siswanto (PT Wahana Global Education, 2026)
Osteoarthritis (OA) is a prevalent chronic inflammatory joint disease in which cyclooxygenase-2 (COX-2) plays a central role in mediating pain and inflammation. Selective COX-2 inhibition offers therapeutic benefit while minimizing gastrointestinal adverse effects associated with non-selective NSAIDs. Naproxen-azetidinone hybrids represent a promising scaffold for developing improved COX-2 inhibitors. Molecular docking was performed against the COX-2 crystal structure (PDB ID: 4M11) using AutoDock Vina, with protocol validation confirmed by redocking (RMSD = 1.0764 Å). MM/GBSA rescoring was applied to estimate binding free energies (ΔGbind). Six naproxen-azetidinone derivatives (N4a-N4f) were evaluated alongside meloxicam, isorhamnetin, and naproxen as references. All derivatives exhibited superior COX-2 binding affinity (docking score: -10.07 to -10.89 kcal/mol; Ki: 0.01032 - 0.04122 µM) and ΔGbind (-51.495 to -55.217 kcal/mol) compared to all references. Arg120 served as the universal hydrogen bond anchor across all derivatives. N4a (docking score: -10.89 kcal/mol: Ki 0.01032 µM) and N4b (ΔGbind : -55.217 kcal/mol) were identified as lead candidates. Naproxen-azetidinone derivatives, particularly N4a and N4b, demonstrate strong in silico potential as selective COX-2 inhibitors superior to meloxicam and isorhamnetin. Experimental validation through enzymatic COX-1/COX-2 inhibition assays and ADMET profiling is warranted.